Strategies For Managing Liquidity Risk Through Asset-Liability Management (ALMA) In Islamic Banking - Fitria Ramadhani; Ilda Ilda (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the causal relationships between integrated asset liability management frameworks and liquidity risk resilience within Islamic commercial banks in Indonesia. Utilizing panel data and partial least squares structural equation modeling, the empirical investigation evaluates how structural maturity gap configurations, funding diversification strategies, and third party fund optimizations determine institutional stability under strict regulatory environments. The empirical findings reveal that while funding diversification introduces short term adjustments within the financing to deposit ratio, active interventions by the internal asset liability committee act as a vital stabilizing mechanism. Furthermore, the banking sector exhibits robust compliance performance, with the mean liquidity coverage ratio and net stable funding ratio systematically exceeding international regulatory baselines without undermining core sharia principles. The results confirm that domestic monetary instruments effectively insulate participating institutions from systemic interbank contagion. This research concludes that the long term financial sustainability of Islamic banking institutions depends on the continuous alignment between disciplined corporate governance and macroprudential liquidity mandates.